Planejamento dos recursos hídricos da bacia hidrográfica do rio Seridó, no Rio Grande do Norte - Melo, Gilson Duarte de (2008)
The present research has the purpose of planning the management of the water resources of the Seridó River watershed, in the state of Rio Grande do Norte, Brazil. It has an emphasis on the amount of surface water available in this region, to provide a sustainable water supply. Based on data and information collected from public departments responsible for the management of the water resources of the Rio Grande do Norte state, well as on researches related to water resources , a watershed balance was done, and the results suggested the transposition of the waters from the Piranhas-Açu river watershed taken from the Oiticica and Armando Ribeiro Gonçalves reservoirs, integrated with the construction of 2 hidroelectrical plants and 2 elevation stations, to pump the amount of water needed to the expected demand in some public dams of the region until 2020. So, with the use of the surface water potential that exists in the region, it was demonstrated that, on the contrary of the public policies implemented in the past and in the current by the federal and state realm, it is possible to supply the currently water demands and also the future ones, in a sustainable way, without the need of importing outter water to the respective watershed. Finally, it was proposed the implementation of the Water Resources Plan in the Seridó region WRPS, aiming at providing an auto-sustainable development by significantly diminishing the effects of the dry seasons in that region, by considering the economic, social and environmental sustainability